Transplantation of Cardicola opisthorchis (Trematoda: Aporocotylidae) sporocysts into the intermediate host, Terebella sp. (Polychaeta: Terebellidae). Issue 1 (February 2017) - Sugihara, Yukitaka; Yamada, Toshiyuki; Iwanaga, Shunsuke; Kanai, Kinya
Abstract: Cardicola opisthorchis is a blood fluke pathogen significantly affecting cultured Pacific bluefin tuna Thunnus orientalis in Japan. It is known that the intermediate host of C. opisthorchis is a terebellid polychaete Terebella sp. In order to study the intrapolychaete larval development of C. opisthorchis, we transplanted sporocysts, which contained a large number of cercariae, of C. opisthorchis obtained from Terebella sp. into sporocyst-free Terebella sp., which had been maintained at 20 °C. The transplanted sporocysts switched from cercarial to sporocystal production by 17 days after transplantation (d.a.t.) and daughter sporocysts were released into the polychaete body cavity at 25 d.a.t. Subsequently, the released daughter sporocysts produced daughter sporocysts again. Thereafter, daughter sporocysts that contained cercariae appeared at 38 d.a.t. and gradually increased. At 51 d.a.t., 136 sporocysts that had multiplied from the original two transplanted sporocysts were observed in the body of one polychaete, and cercariae were released from daughter sporocysts inside the polychaete body cavity. Subsequently the cercariae were found to be released outside the polychaete at 57 d.a.t. This is the first successful case of in situ observation of the development of a blood fluke within the intermediate host. Graphical abstract: Highlights: We transplanted C. opisthorchis sporocysts into sporocyst-free polychaete host. Transplanted sporocysts switched from cercarial to sporocystal production. Sporocysts multiplied to 136 from the two transplanted sporocysts. Daughter sporocysts produced cercariae, which were released outside the polychaete.